กลไกการสร้างเครือข่ายศูนย์ติดตามข่าวปลอมที่เกี่ยวกับอิสลาม เพื่อลดผลกระทบการดำเนินชีวิตของมุสลิมในประเทศไทย: กลไกการสร้างเครือข่ายศูนย์ติดตามข่าวปลอมที่เกี่ยวกับอิสลาม เพื่อลดผลกระทบการดำเนินชีวิตของมุสลิมในประเทศไทย - Serpa, Nabavee; ราโอบ อิสมาอีล; สองเมือง จารุวัจน์; แยนา ซัยฟุดดีน; บารู มูฮำหมัดศอฟรี; บารู มูฮำหมัดศอฟรี (Al-HIKMAH Journal, 2022)
This study aims to establish mechanism and a network of Islamic Fake News Monitoring Center (IFMC). 3 groups of participants participated in this study: 1) a group of associated network monitoring online Islamic news, 2) a group of associated advisory network of IFMC for information approval, and 3) a gorop of safe and creative media producer network. All three groups have signed Memorandum of Understanding (MoU) to collaborate with IFMC: Islamic Fake News Monitoring Center. The results showed that the mechanism of establishment of IFMC is initiated from a group of associated network monitoring online Islamic news by, reporting information or evidence of Islamic fake news through website or social media of the center. The IFMC, then, sent those information or evidence to committee and advisory group to investigate, examine and approve based on the Holy Quran and Hadith. The approved news is sent to a group of safe and creative media producer network including Islam Nara, White Channel, FTU TV, and Thailand Narathiwat Radio to create various and understandable forms of media. Lastly, those approved news are published on IFMC website and social media to present the fact or fake news to Muslim and non-Muslim community. These allowed them to comply with Islamic principle and reduce the impacts occured from Islamic. Fake news. Keywords : Mechanism to build network, Fake News, Islam